Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Guest Column: The 7 faces of quantum NP - Gharibian, Sevag (ACM SIGACT News)
When it comes to NP, its natural definition, its wide applicability across scientific disciplines, and its timeless relevance, the writing is on the wall: There can be only one. Quantum NP, on the other hand, is clearly the apple that fell far from the tree of NP. Two decades since the first definitions of quantum NP started rolling in, quantum complexity theorists face a stark reality: There's QMA, QCMA, QMA1, QMA(2), StoqMA, and NQP. In this article aimed at a general theoretical computer science audience, I survey these various definitions of quantum NP, their strengths and weaknesses, and why most of them, for better or worse, actually appear to fit naturally into the complexity zoo.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)